Diagnosis, Panduan dan Tindakan Koheren Dalam Strategi Penertiban Parkir Liar Oleh Dinas Perhubungan Kota Padang - Madeleine Cania; Roni Ekha Putera; Yoserizal Yoserizal (Indonesian Journal Publisher, 2022)
This study aims to identify and describe the strategy for controlling illegal parking by the Padang City Transportation Service. This research uses descriptive qualitative method. The data collection technique used in this research is to conduct observations, interviews and documentation. While the data validity technique uses source triangulation. The theoretical basis that becomes the analytical knife in this research is the core theory of strategy proposed by Rumeltwhich consists of diagnosis, guiding policy and coherent action. The result of this research is that it can be seen that the Padang City Transportation Service has fulfilled the three variables of the core strategy theory proposed by Rumelt. The Padang City Transportation Service has implemented a strategy in an effort to control illegal parking in the city of Padang quite well, but there are some shortcomings so that the strategy that has been carried out has not been running optimally. The strategy for controlling illegal parking by the Padang City Transportation Service is to take actions such as locking tires, deflation of tires, and towing or moving vehicles. Overall, the actions taken were able to become one of the efforts of the Padang City Transportation Service in realizing its strategic target, namely improving traffic performance in the city of Padang.